Efficacy of recombinant VAXXITEK HVT-IBDv vaccine against very virulent Infectious bursal disease virus (vvIBDv) challenge in layer chicks: A pilot study - DAČIĆ, M.; RESANOVIC, R.; RASIC, Z.; VALCIC, M.; MILOVANOVIC, A.; VELHNER, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
The infectious bursal disease virus (IBDv) is widespread in poultry flocks all around the world. Various biotypes have emerged and because of that, adequate management practices and vaccination of chicks are of paramount importance for the protection against field strains. One day old Lohmann Brown chicks were vaccinated with intermediate vaccines and the recombinant VAXXITEK HVT-IBDv vaccine formulation, and challenged at 48 days of life with the very virulent IBDv (vvIBDv) strain CH/99. The best protection (100%) was achieved with the recombinant vaccine administered by the subcutaneous or intramuscular route at a day old, while intermediate and intermediate plus vaccines protected 80% of birds from clinical symptoms. The highest bursa body ratio (5.33, 3.50 and 4.12) was accomplished in non- vaccinated and non-challenged birds and birds vaccinated with the VAXXITEK HVT-IBDv vaccine. The recombinant VAXXITEK HVT-IBDv vaccine has provided protection for commercial chicks against challenge with the vvIBDv strain in this experiment. Under field conditions, additional vaccination is possibly needed with supplementary application of live attenuated vaccines. However, the recombinant vector vaccines are providing significant aid against clinical signs and immunosupression caused by the vvIBDv.